EKSISTENSI HUKUM YANG BERLANDASKAN KONSTITUSI DI INDONESIA - Pakpahan, Zainal Abidin (Jurnal Ilmiah Advokasi, 2025)
The constitution is the basic law and the highest law in a country, every citizen and state power organizer must submit to the constitution which is the guideline in state life. The existence of the constitution as one of the elements of the state reflects a state of law because in the constitution it regulates the protection of human rights, the existence of the principles of freedom, equality, openness, justice and the existence of limitations on the power of state organizers so that the law as a rule is not something that just comes, but the law comes from society which is used to regulate the form of relations between humans so that humans cannot escape from the bonds that exist in the midst of social life, and therefore, it is a reality that must be recognized that where there is society, there must be laws that are based on the constitutionKeywords: Existence, Law, Constitution, State